PENGARUH KONDISI INTERNAL SEKOLAH DAN DUKUNGAN EKSTERNAL TERHADAP INOVASI PEMBELAJARAN DI SMK MUHAMMADIYAH 4 AL AMIN BANJARMASIN - Lisa Hartini; Suriansyah, Ahmad; Purwanti, Ratna (Komunitas Manajemen Kompetitif, 2025)
This study examines the influence of internal school conditions and external support on learning innovation at SMK Muhammadiyah 4 Al Amin Banjarmasin. Learning innovation is the main key to improving the quality of vocational education in the digital era. This study uses a qualitative approach with a case study to understand the dynamics of learning innovation implementation. Data were collected through observation, in-depth interviews with the principal, teachers, and students, and analysis of school documents. The research findings indicate that internal school conditions including principal leadership, teacher competence, learning facilities, and school culture have a significant effect on the implementation of learning innovation. External support from the government, the business world and industry (DUDI), and the community also make a positive contribution to the development of learning innovation. The results of the study indicate that the synergy between strong internal conditions and ongoing external support is a determinant factor in the success of learning innovation at SMK Muhammadiyah 4 Al Amin Banjarmasin